Exploring the Management of Digital Dakwah in an Islamic Boarding School: A Case Study of AL Jauharen Jambi - Jakaria Jakaria; Eddy Haryanto; Masbirorotoni Masbirorotoni (Journal of Educational Sciences, 2026)
Despite the growing body of literature on digital dakwah in pesantren, limited research has examined how digital dakwah is managed as an organizational process involving leadership, human resources, and media production systems. This study aims to explore the management of digital dakwah practices at Al Jauharen Islamic Boarding School, Jambi, Indonesia. A qualitative case study approach was employed involving eight participants, including pesantren leaders, ustadz, multimedia-involved santri, and media administrators. Data were collected through semi-structured interviews, non-participant observations, and document analysis and were analyzed using thematic analysis involving data reduction, data display, and conclusion drawing. The findings reveal three major challenges in managing digital dakwah: limited technological infrastructure, low digital literacy among ustadz and santri, and the absence of standardized procedures for content production. Despite these challenges, the pesantren demonstrates a strong commitment to developing digital dakwah through platforms such as TikTok, Instagram, YouTube, Facebook, and live-streaming activities. The study concludes that effective digital dakwah management requires the integration of infrastructure development, human resource capacity building, and organizational system strengthening. This research contributes empirical evidence on the management dimensions of digital dakwah in pesantren and provides practical insights for Islamic educational institutions adapting to digital transformation.